HISTORY OF HANTAVIRUS - Moulishree,; Jothipriya,; K. R. , Don (International Journal of Psychosocial Rehabilitation, 2020)
Hantavirus is an expanding group of virus species. It can cause various clinical manifestations mainly categorized as hemorrhagic fever with renal syndrome and hantavirus pulmonary syndrome. It belongs to the family Bunyaviridae that gets transmitted through rodents, bats, and several insectivore species. There are various species that are getting discovered on a regular basis. There are various immune responses noticed due to the intervention of hantavirus in a host There are various commercial vaccines found against hantavirus, in which HANTAVAX is a Korean commercial vaccine. Further, the traces and history of the hantavirus infections in various geographic locations are discussed. So this review aims to study the history of hantavirus, its structural and functional aspects, and its effect over the world; public health is discussed, and awareness is spread about the same.